Responsive social support serves important functions in clinical communication: Translating perspectives from relationship science to improve cancer clinical interactions. (December 2022) - Dwyer, Laura A.; Epstein, Ronald M.; Feeney, Brooke C.; Blair, Irene V.; Bolger, Niall; Ferrer, Rebecca A.
Abstract: Patient-clinician interactions are critical to patient-centered care, including in cancer care contexts which are often defined by multiple patient-clinician interactions over an extended period. Research on these dyadic interactions has been guided by perspectives in clinical communication science, but the study of clinical communication has not been fully integrated with perspectives on interpersonal interactions from relationship science research. An overlapping concept in both fields is the concept of responsive social support . In this article, we discuss responsiveness as a concept that offers opportunities for connections between these two disciplines. Next, we focus on how relationship science can be applied to research in clinical settings. We discuss how three areas of relationship science define responsiveness and have potential for extension to clinical communication: (1) (in)visibility of social support, (2) attachment orientations, and (3) shared meaning systems. We also discuss how social biases can impede responsiveness and suggest research avenues to develop ideas and understand potential challenges in connecting these two fields. Many opportunities exist for interdisciplinary theory development that can generate momentum in understanding interpersonal processes in cancer care. Highlights: Research in clinical communication and close relationships have been distinct. Responsiveness is an overlapping theme in both fields. Areas from relationship science can potentially inform clinical communication. Research needs include studying avenues for connecting these two fields.